Decoding LY6G6D in colorectal cancer: Unraveling biomarker potential and therapeutic insights: LY6G6D in colorectal cancer - Naqvi, Mehwish; Abbasi, Waqas Ahmad; Samma, Muhammad Kaleem; Gabol, Asif Ali; Innocent, Cynthia; Iqbal, Sana; Fatima, Samana; Ali, Kashif (Cellular and Molecular Biology, 2024)
Colorectal cancer (CRC) poses a significant global health challenge with high morbidity and mortality rates. This study investigates the role of LY6G6D, a member of the LY6/uPAR superfamily, in CRC. Employing a bioinformatic approach, we analyzed LY6G6D expression across different cancer types, compared it with known oncogenes in CRC, explored the involved genomic alterations, and assessed associated clinicopathological characteristics. LY6G6D exhibited aberrant expression, particularly elevated in CRC adenocarcinoma and highly specific to tumor tissues when compared with other oncogenes, despite its comparatively low frequency of genomic alteration. Subsequently, tumor immune infiltration analysis revealed distinct associations, primarily indicating a negative correlation, suggesting immune down-regulation. Survival analysis in context of LY6G6D was conducted with Kaplan-Meier (KM) curves, indicating a 10% risk of disease recurrence in the case of elevated expression. Additionally, we constructed a 3D protein model of LY6G6D through ab-inito approach. The protein model was validated, followed by conservation analysis and active site identification. Active site identification of LY6G6D’s final predicted model revealed some similar sites that were estimated to be conserved. Target-guided drug molecules were collected and molecular docking was executed, proposing Cardigin (Digitoxin) and Manzamine A as potential therapeutic candidates. In conclusion, LY6G6D emerges as a significant biomarker for diagnostic and therapeutic applications in CRC, highlighting its multifaceted role in tumorigenesis. The proposed drugs present avenues for further investigations.